Connecting the Dots: Pain Mental Models of Spousal Caregivers of Veterans with Dementia and Pain. (17th December 2021) - Block, Phoebe; Shrestha, Srijana; Evans, Tracy; Hilgeman, Michelle; Loup, Julia; Kunik, Mark; Snow, A Lynn
Abstract: Pain is prevalent among persons with dementia (PWDs), yet often goes underrecognized and undertreated. Exploring caregivers' pain mental models may provide valuable insight into how they conceptualize pain, and how such conceptualizations affect their identification of and response to PWDs' pain. We identified and described the pain mental model(s) of spousal caregivers of community-dwelling veterans with dementia and pain through a secondary qualitative thematic analysis of recordings of a psychosocial intervention aimed at preventing aggression in PWDs with pain. Thirty female spousal caregivers (11 Black, 10 non-Hispanic White, and 9 Hispanic) comprised the present sample. Two themes were identified: Pain Assessment Beliefs and Knowledge (PA) and Pain Management Beliefs and Knowledge (PM). In our proposed mental model framework, PA and PM affect the ways caregivers answer two PA-related questions (Is there a problem?, Is this problem pain?) and three PM-related questions (Is the pain treatable?, Is it worth treating?, How do I prefer to treat it?). Caregivers are moved to action when they "connect the dots" by identifying a problem in PWDs' behavior, labeling the problem as pain, and identifying a response (i.e., a treatment approach) they consider worth trying. Disconnects in caregiver understanding of PWDs' behavior are common in this sample, and predictably lead to inaction. The proposed mental model provides further explanation about how caregivers do or do not synthesize and apply pain knowledge and experience, allowing for the identification of potential areas of intervention (e.g., pain psychoeducation) to improve pain treatment for the PWDs under their care.